Transcatheter aortic valve implantation: role of multimodality cardiac imaging. (January 2010) - Delgado, Victoria; Ng, Arnold CT; Shanks, Miriam; van der Kley, Frank; Schuijf, Joanne D; van de Veire, Nico RL; Kroft, Lucia; Roos, Albert de; Schalij, Martin J; Bax, Jeroen J
Current evidence based on more than 8000 high-risk patients with severe aortic stenosis has demonstrated that transcatheter aortic valve implantation (TAVI) is a feasible alternative to surgical aortic valve replacement in selected patients. Despite current promising results on hemodynamic and clinical improvements, there are several unresolved safety issues, such as the frequency of vascular complications, postprocedural paravalvular leak, atrioventricular heart block and stroke. Multimodality cardiac imaging may help to minimize these complications and may play a central role before (optimizing patient selection, selection of appropriate prosthesis size and anticipating the procedural approach), during and after TAVI (evaluating the immediate and long-term procedural results). This article reviews the state-of-the-art TAVI procedures and the role that multimodality cardiac imaging plays before, during and after TAVI.